Pricing formula for power options with jump-diffusion - Ibrahim, Siti Nur Iqmal; O’Hara, John G.; Mohd Zaki, Muhammad Syazwan (Natural Sciences Publishing, 2016)
Payoff of a power option is typified by its underlying share price raised to a constant power. Also known as leveraged option, a minor change in its underlying may lead to a significant change in its price. In this study, we derive pricing formula for power options using the martingale approach when the underlying asset follows a jump-diffusion process.